Մշակութային ցեղասպանության իրագործման մեխանիզմները 1909թ. Ադանայի և հարակից շրջանների կոտորածների ընթացքում և դրանց հետևանքները - Պարսամյան, Սեդա (ՀՀ ԳԱԱ Հայոց ցեղասպանության թանգարան-ինստիտուտ)
Numerous facts testify that during the Hamidian massacres of 1894-1896, and the Adana massacres of 1909, as well as during the Armenian Genocide (1915-1923) massacres were accompanied by the destruction of the Armenian cultural monuments, values; namely, the demolition of schools and historical-architectural monuments, which completely fits with the description of the cultural genocide.
Keywords: Հայոց ցեղասպանություն; Հայոց պատմություն